The Enculturation Sasando At Haleluya Music Course Institute East Nusa Tenggara (Universitas Negeri Semarang, 2022)
Haleluya Music Course Institute is a music course intitute located in Kupang, East Nusa Tenggara province which provides Sasando lessons and opportunities for students to take part in Sasando performances at festivals, government events and other events. This study aimed to investigate the history and enculturation of Sasando performances. The qualitative research method was implemented with these data collecting techniques, i.e., observation, interview, documentation and document study. The results of the initial research showed the functions of Sasando as an auxiliary, support or accompanist in a poetry reading (Sasando gives life to the poem being read). Mr. Djony Theedens is interested to develop the use of Sasando through a course institute to bestow the musical instrument for the younger generations and avoid its extinction. It is done through the teaching of this instrument from the older generation to the younger one. The teaching is done to prevent its extinction and pass on the knowledge to future generations. Apart from that, the enculturation process of Sasando is also carried out through Sasando performances by the students from the course institute. Through the performances, the enculturation of Sasando occurs. Further, the distribution of cultural values ​​also happens through the performances.